Infrared LED Enhanced Spectroscopic CdZnTe Detector Working under High Fluxes of X-rays - Pekárek, Jakub (Sensors (Basel), 2016)
This paper describes an application of infrared light-induced de-polarization applied on a polarized CdZnTe detector working under high radiation fluxes. We newly demonstrate the influence of a high flux of X-rays and simultaneous 1200-nm LED illumination on the spectroscopic properties of a CdZnTe detector. CdZnTe detectors operating under high radiation fluxes usually suffer from the polarization effect, which occurs due to a screening of the internal electric field by a positive space charge caused by photogenerated holes trapped at a deep level. Polarization results in the degradation of detector charge collection efficiency. We studied the spectroscopic behavior of CdZnTe under various X-ray fluxes ranging between [Formula: see text] and [Formula: see text] photons per mm [Formula: see text] per second. It was observed that polarization occurs at an X-ray flux higher than [Formula: see text] mm [Formula: see text] ·s [Formula: see text]. Using simultaneous illumination of the detector by a de-polarizing LED at 1200 nm, it was possible to recover X-ray spectra originally deformed by the polarization effect.